The Relationship Between Cultural Intelligence and Teaching Effectiveness of Chinese and Foreign Teachers - Wenpeng , Lyu; Pupat, Nathaya (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
The purpose of this research was to understand the relationship between cultural intelligence and teaching effectiveness and conduct analysis to measure teaching effectiveness. This paper uses survey to collect data for applying statistical analysis techniques to analyse the cultural intelligence that influence the teaching effectiveness and promotion of Chinese and foreign teachers in Heilongjiang International University. The conceptual framework in this paper included Cultural Intelligence (CQ), Metacognitive Cultural Intelligence (MCQ1), Cognitive Cultural Intelligence (CCQ), Motivated Cultural Intelligence (MCQ2), and Action Cultural Intelligence (BCQ). Questionnaires were distributed to teachers of Heilongjiang International University totalling 200 (N=200). The reliability and validity of the questionnaire were conducted. Regression analysis was performed to test the causal relationship between the key variables and the rationality of hypothesis. The overall reliability coefficient of the scale is 0.946, which is greater than 0.8, and has good reliability as shown in table1. The findings show that the scales used to measure cultural intelligence reliable. From the results of Likert scale, metacognitive cultural intelligence has a higher score of 3.5525, and the teaching effectiveness has a relative high score of 3.326. It is clearly that the cultural intelligence has a positive relationship with teaching effectiveness. In the regression analysis, the R square value is 0.765, which indicates that the MCQ1, CCQ, MCQ2 and BCQ can explain 76.5% of the teaching effectiveness. So the teaching effectiveness can be enhanced through strengthening the cultural intelligence.